2004
DOI: 10.1111/j.1600-6143.2004.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Sparing with Tacrolimus and Mycophenolate Mofetil in Renal Transplantation

Abstract: Evidence suggests that steroid sparing in renal transplantation is associated with good outcomes, although there are limited data regarding steroid sparing in Tacrolimus and Mycophenolate Mofetil (MMF)-based regimes. In this study we describe the use of these agents in 101 consecutive patients undergoing renal transplantation using only a 7-day course of prednisolone.Median follow-up was 33 months (range 18-44). Patient and graft survival at 1 year were 100% and 98%, respectively. The acute rejection rate at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Birkeland (24) and Khwaja et al (30) reported excellent longterm graft survival and function (3 and 4 yr, respectively) with very low rejection rates. In other studies, a slight increase in acute rejection episodes, especially in the early posttransplantation period, was observed; these were easily reversible, and their impact on long-term graft survival is unclear at this time (27,(31)(32)(33)(34). In this context, we recently published a retrospective analysis from our transplant center of an examination of the impact of two different induction agents, alemtuzumab (Campath 1H, Berlex Laboratories, Wayne, NJ) versus basiliximab (Simulect, Novartis Pharmaceuticals, East Hanover, NJ) on long-term patient and graft survival for patients who were maintained on prednisone-free immunosuppression with tacrolimus and MMF (35).…”
mentioning
confidence: 89%
“…Birkeland (24) and Khwaja et al (30) reported excellent longterm graft survival and function (3 and 4 yr, respectively) with very low rejection rates. In other studies, a slight increase in acute rejection episodes, especially in the early posttransplantation period, was observed; these were easily reversible, and their impact on long-term graft survival is unclear at this time (27,(31)(32)(33)(34). In this context, we recently published a retrospective analysis from our transplant center of an examination of the impact of two different induction agents, alemtuzumab (Campath 1H, Berlex Laboratories, Wayne, NJ) versus basiliximab (Simulect, Novartis Pharmaceuticals, East Hanover, NJ) on long-term patient and graft survival for patients who were maintained on prednisone-free immunosuppression with tacrolimus and MMF (35).…”
mentioning
confidence: 89%
“…Birkeland and Khwaja reported excellent long term graft survival and function (3 and 4 year, respectively) with very low rejection rates. In other studies, a slight increase in acute rejection episodes, especially in the early posttransplantation period, was observed; these were easily reversible, and their impact on long-term graft survival is unclear at this time (Borrows et al, 2004;Cole et al, 2001;Grewal et al, 1998;ter Meulen et al, 2004). Steroids, once thought to be a mandatory component of immunosuppression to preserve graft survival, are gradually being eliminated from current protocols.…”
Section: Interactions Between Glucocorticoids and Tacrolimusmentioning
confidence: 99%
“…It has been demonstrated that such approaches have reduced cardiovascular mortality without compromising graft survival,34 although there is a higher reported incidence of acute rejection in some patient groups such as African Americans.…”
Section: Immunosuppressive Therapymentioning
confidence: 99%